Analisis Usahatani Pakcoy (Brassica rapa L.) Pada Sistem Urban Farming - Chintia, Aksho Citra; Efrita, Edi; Kurniati, Novitri; Marwan, Edy (Jurnal MeA (Media Agribisnis), 2025)
Agricultural land in Indonesia is decreasing due to land conversion into housing and other public facilities.. The scarcity of agricultural land is especially felt in urban areas, so the remaining land must be utilized optimally and efficiently. Urban farming is an agricultural or plantation concept that is carried out using limited land. The principle of urban farming is any effort to utilize space or land that still exists in urban areas, such as yards, roofs or walls of houses. Urban agricultural cultivation methods can be carried out using verticulture, hydroponics, aquaponics, aeroponics, fruit plants in pots (tabulampot) or polybags, and others. The aim of this research is to study the concept of urban farming using several methods, namely: (1) polybags (2) vertical cultivation (3) wall plant bags (4) hydroponic Deep Flow Technique (DFT) in urban farming areas. The data used is data from the results of an Independent Certified Internship at the Center for Implementation of Standard Agricultural Instruments in Bengkulu which was carried out from September to January 2024. Analysis of the data used includes (1) profit (2) R/C Ratio (3) B/C Ratio (4) Break Event Point (BEP). Based on the conclusions of the analysis of pakcoy farming with an urban farming system using polybag, wall planter bag, verticulture, Hydroponic Deep Flow Tenchnique (DFT) techniques, it was stated that of the four pakcoy cultivation techniques there was one technique that was declared inefficient to carry out or not feasible because it has value. profit 20,688.89, R/C Ratio 1.35, B/C Ratio 0.35 and Break even point Product BEP 2.97 kg and Revenue BEP IDR 59,311.11 which is a smaller value.